Hydrogen storage in complex hydrides: past activities and new trends. (1st July 2022) - Dematteis, Erika Michela; Amdisen, Mads B; Autrey, Tom; Barale, Jussara; Bowden, Mark E; Buckley, Craig E; Cho, Young Whan; Deledda, Stefano; Dornheim, Martin; de Jongh, Petra; Grinderslev, Jakob B; Gizer, Gökhan; et al.
Abstract: Intense literature and research efforts have focussed on the exploration of complex hydrides for energy storage applications over the past decades. A focus was dedicated to the determination of their thermodynamic and hydrogen storage properties, due to their high gravimetric and volumetric hydrogen storage capacities, but their application has been limited because of harsh working conditions for reversible hydrogen release and uptake. The present review aims at appraising the recent advances on different complex hydride systems, coming from the proficient collaborative activities in the past years from the research groups led by the experts of the Task 40 'Energy Storage and Conversion Based on Hydrogen' of the Hydrogen Technology Collaboration Programme of the International Energy Agency. An overview of materials design, synthesis, tailoring and modelling approaches, hydrogen release and uptake mechanisms and thermodynamic aspects are reviewed to define new trends and suggest new possible applications for these highly tuneable materials.